The Impact of 5G Technology on Interactive Mobile Applications A Case Study of Smart Cities - Tavui, Samuela; Vakalalabure, Laisa (Journal Mobile Technologies (JMS), 2025)
The study examines the implementation of fifth-generation (5G) communication networks as a transformative enabler of interactive mobile applications in Fiji’s developing smart city ecosystem. Integrating theoretical and empirical perspectives, the research formulates a hybrid analytical framework that combines technical, organizational, and socio-technical dimensions to assess system efficiency, cultural usability, and sustainability. Using a constructive case study design, supported by the modified FITT model and triangulated validation, the findings demonstrate that 5G deployment in Fiji achieved notable performance outcomes, including a 12.8-minute small-cell configuration time, 98.2% beamforming accuracy, and an 87/100 Melanesian System Usability Scale (SUS-M) score. These results confirm that localized technological adaptation, when aligned with cultural usability and responsive governance, enhances both reliability and community acceptance. However, challenges persist in energy optimization (5.2 W per cell) and cybersecurity, where a vulnerability index of 0.42 indicates the need for post-quantum encryption measures. The proposed Techno-Cultural Symbiosis Model emphasizes that sustainable 5G implementation in island contexts depends on balancing technological precision, socio-cultural relevance, and ecological responsibility. The resulting roadmap outlines a phased national strategy (2026–2030) integrating AI-driven spectrum management, cultural usability certification, and post-quantum cryptography to advance secure, inclusive, and sustainable digital transformation across the Pacific region.